2018
DOI: 10.1212/wnl.0000000000006544
|View full text |Cite
|
Sign up to set email alerts
|

Who should undergo a comprehensive cognitive assessment after a stroke?

Abstract: ObjectiveTo validate the ability of a specifically developed cognitive risk score to identify patients at risk of poststroke neurocognitive disorders (NCDs) who are eligible for a comprehensive cognitive assessment.MethodsAfter assessing 404 patients (infarct 91.3%) in the Groupe de Réflexion pour l'Evaluation Cognitive VASCulaire (GRECogVASC) cross-sectional study with the National Institute of Neurological Disorders and Stroke–Canadian Stroke Network battery 6 months after stroke, we used multivariable logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
2
11
0
3
Order By: Relevance
“…A comprehensive neuropsychological assessment was performed by a neuropsychologist according to the GRECoGVASC battery (15, 16), a French-language adaptation and standardization of the National Institute of Neurological Disorders and Stroke–Canadian Stroke Network comprehensive battery (17). Several cognitive domains were explored: visuospatial and visuoconstructive skills assessed by the Rey Figure, episodic memory (verbal and visual) evaluated by the RL/RI-16 test [French adaptation of the Free and Cued Selective Reminding Test of Gruber and Buschke (18)] for the verbal modality and memory reproduction of the Rey figure for the visual modality (19), executive functions evaluated by the Trail Making Test (TMT) (20), the Subtest of Codes from Wechsler adult intelligence scale (WAIS-IV) (21), and the Verbal Fluences (categorical and lexical) (22).…”
Section: Methodsmentioning
confidence: 99%
“…A comprehensive neuropsychological assessment was performed by a neuropsychologist according to the GRECoGVASC battery (15, 16), a French-language adaptation and standardization of the National Institute of Neurological Disorders and Stroke–Canadian Stroke Network comprehensive battery (17). Several cognitive domains were explored: visuospatial and visuoconstructive skills assessed by the Rey Figure, episodic memory (verbal and visual) evaluated by the RL/RI-16 test [French adaptation of the Free and Cued Selective Reminding Test of Gruber and Buschke (18)] for the verbal modality and memory reproduction of the Rey figure for the visual modality (19), executive functions evaluated by the Trail Making Test (TMT) (20), the Subtest of Codes from Wechsler adult intelligence scale (WAIS-IV) (21), and the Verbal Fluences (categorical and lexical) (22).…”
Section: Methodsmentioning
confidence: 99%
“…Although this is always a clinical indication, and should, in the end, based on the individual level, some cues can be given: this objective can be achieved using a recently explored strategy based on risk factors of PSCI (Table 1 provided in supplementary material, and “Predictors” section). 21 Several factors have been found to be associated with PSCI, major CI, in particular. 10,16,22 A recent study has identified a minimal set of factors for selecting patients at risk of full-spectrum PSCI.…”
Section: Resultsmentioning
confidence: 99%
“…10,16,22 A recent study has identified a minimal set of factors for selecting patients at risk of full-spectrum PSCI. 21 The Rankin score represents an important step provided it is graded with a reliable informant, using a structured interview (including difficulties in instrumental activities of daily living). 23 Except in specific situations (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the MoCA, (or other short tests) may be appropriate in the assessment of patients with mild cerebrovascular events (TIA and minor non-disabling stroke) [12], or in the detection of longer-term post stroke cognitive impairment when the number of survivors with severe stroke and problems interfering with the use of brief tests, is small [13]. Short screening tests including the MoCA may also help as an initial screening tool after acute stroke in pragmatic large-scale studies in predicting longer-term cognitive and functional outcome, or to guide need for further in-depth assessment [14,15]. In contrast, the OCS is more appropriate for informing the management of patients with acute severe stroke who will require extensive rehabilitation.…”
mentioning
confidence: 99%